Green banking initiatives: The role of CSR in aligning with the SDGs and shaping sustainable consumer choices - Hao Wu; Norzieiriani Ahmad; Nazlina Zakaria (Acta Psychologica, 2025)
This study examines how corporate social responsibility (CSR) influences green purchase intentions in the banking services, aligning with the United Nations' Sustainable Development Goals (SDGs). The research highlights CSR's impact on green buying decisions, focusing on the mediating effects of green perceived value and gratitude, and the moderating role of green altruism. Data from 315 banking consumers was collected and analyzed via SMART-PLS. The findings indicate that CSR enhances green purchase intentions, with green perceived value and gratitude as mediators, and green altruism as a moderator. Banks can leverage CSR to promote green purchases, increasing customer loyalty while fostering environmental behaviors. Fostering green altruism enhances CSR's impact. This research confirms the banking sector's key role in achieving SDGs through CSR, managing sustainable consumption and production. The study introduces an integrated model of green perceived value, gratitude, and green altruism, contributing to the broader literature on green sustainability in banking.